Impact of scarification on soil physical quality and sugarcane production in southeastern Brazil - Melo, Nilvan C. (2025)
Soil preparation operations alter soil structure and incur high costs in sugarcane field renovation; as such, there is a need for measures that lower costs and provide favorable conditions for sugarcane development. Thus, the present study aimed to assess the impact of row and full-area scarification on the physical quality indicators of Oxisol and Ultisol, stalk yield, and recoverable total sugar in sugarcane plants. The experiment was conducted in two areas in São Paulo state (SP), Brazil. The experimental design was based on large paired plots with two treatments: soil scarification in the planting row and over the total area, in both soil types. Soil samples were collected from the 0.00-0.10 m and 0.10-0.20 m layers in both areas. Sand, silt, and clay contents were determined, as well as soil bulk density, macroporosity, microporosity, and soil penetration resistance, six months after planting. Additionally, sugarcane yield and recoverable total sugar content were assessed. Based on the results, a multivariate factor analysis was conducted using principal component analysis (PCA). Physical attributes were similar in both soils, regardless of scarification site. Row scarification can replace its full-area counterpart, since average sugarcane stalk yield and recoverable total sugar content were similar in both soil types, regardless of scarification location.